2019
DOI: 10.1016/j.cmet.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane 4 L Six Family Member 5 Senses Arginine for mTORC1 Signaling

Abstract: Highlights d TM4SF5 acts as a membrane-based sensor for lysosomal arginine levels d TM4SF5 promotes mTOR enrichment at lysosomes upon amino acid repletion d TM4SF5 binds mTOR, SLC38A9, and arginine under physiological arginine levels d TM4SF5-and SLC38A9-mediated arginine efflux promotes mTOR/S6K1 growth signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 48 publications
1
78
0
Order By: Relevance
“…mLST8 is associated with the catalytic domain of mTOR and may stabilize the kinase activation loop, DEPTOR on the contrary inhibits mTOR activity, TTI1/TEL2 is a mTOR interacting protein important for mTOR stability and assembly of the mTOR complex and maintain their activities (28) (Figure 1). mTORC1 is activated via growth factors stimulation [epidermal growth factor (EGF), insulin-like growth factor (IGF)], increase in amino acid levels such as leucin and arginine and cellular energy status (29)(30)(31), promoting protein and lipid synthesis, as well as ribosome biogenesis impacting on cell proliferation and growth, autophagy and metabolic processes are also stimulated by mTORC1 action (32). Moreover, it was demonstrated that mTORC1 signaling is strongly implicated in the aging process of diverse organisms, including yeast, worms flies, and mammals (33).…”
Section: Structure and Functions Of Mtorc1mentioning
confidence: 99%
“…mLST8 is associated with the catalytic domain of mTOR and may stabilize the kinase activation loop, DEPTOR on the contrary inhibits mTOR activity, TTI1/TEL2 is a mTOR interacting protein important for mTOR stability and assembly of the mTOR complex and maintain their activities (28) (Figure 1). mTORC1 is activated via growth factors stimulation [epidermal growth factor (EGF), insulin-like growth factor (IGF)], increase in amino acid levels such as leucin and arginine and cellular energy status (29)(30)(31), promoting protein and lipid synthesis, as well as ribosome biogenesis impacting on cell proliferation and growth, autophagy and metabolic processes are also stimulated by mTORC1 action (32). Moreover, it was demonstrated that mTORC1 signaling is strongly implicated in the aging process of diverse organisms, including yeast, worms flies, and mammals (33).…”
Section: Structure and Functions Of Mtorc1mentioning
confidence: 99%
“…TM4SF5, LARS, and SAMTOR are cytosolic arginine, leucine, and S-adenosylmethionine sensors, respectively membrane, where it interacts with TOR and the SLC38A9 in an arginine-regulated manner. This interaction further causes arginine efflux and actives TORC1 (Jung et al 2019).…”
Section: Figmentioning
confidence: 99%
“…Recently, the discoveries of SLC38A9, Sestrins, CASTOR1, SAMTOR, Transmembrane 4 L Six Family Member 5 (TM4SF5), and leucyl-tRNA synthetase (LARS) represent the dawn of the age of amino acid sensors ( Fig. 3) Han et al 2012;Jung et al 2019;Zheng et al 2016).…”
Section: Figmentioning
confidence: 99%
“…ATRAID is, like LAMP1, GLMP and OSTM1, a type I transmembrane protein (Figure 2). SLC38A9, a central core of the amino acidsensing machinery [73] interacts with the highly N-glycosylated tetraspanin TM4SF5 [74], but if it acts as an essential accessory subunit needs further investigation. It should be noted that an interaction of SLC38A9 has also been shown with the V-ATPase and NPC1 [73,75].…”
Section: Accepted Articlementioning
confidence: 99%